Transformative justice in a settler colonial transition: implementing the UN Declaration on the Rights of Indigenous Peoples in Canada. Issue 2 (7th February 2022) - Nagy, Rosemary
ABSTRACT: The transformative justice agenda within the field of transitional justice has yet to take up settler colonialism and Indigenous peoples. This paper develops the idea of an indigenised, decolonial transformative justice that encompasses relational change at the grassroots level through acts of Indigenous resurgence, settler decolonisation and allyship, as well as structural transformations at the state and global levels through the UN Declaration on the Rights of Indigenous Peoples. Canada currently is in a transitional moment and there has been a perceptible shift in its position toward the Declaration. It originally voted against the Declaration but is now committed to implementation as per the Truth and Reconciliation Commission's recommendation. A key issue is the extent to which the Declaration will be subsumed under Section 35 of the Constitution, which recognises existing Aboriginal Rights. The paper argues that Section 35 can only become a 'full box of rights' if the lid is fully opened to embrace the transformative, decolonising provisions of the Declaration, particularly those around free, prior and informed consent. Given the apparent reluctance of the state to disrupt the colonial status quo, grassroots and transnational mobilizations and strategies that enact the performative element of Indigenous rights will remain key.